Uprising - Speny, Cailee; 1986-; Eastwood, Scott; Boyega, John; DeKnight, Steven S (Universal City, CA, 2018)
When Earth is once again threatened by large monsters, a former Jaeger pilot rejoins the force to defend the planet.
Keywords: Robots; Mecha (Vehicles); Drama; Monsters; Drama; Drama